PENGARUH KONSENTRASI URIN KELINCI DAN BOKASI PUYUH TERHADAP KANDUNGAN KLOROFIL DAUN DAN HASIL TANAMAN BLUMKOL (Brassica oleracea var. botritys L.) - Noviana Riyanti; Yacobus Sunaryo; Darnawi (Universitas Sarjanawiyata Tamansiswa, 2023)
This research aims to determine the influence of giving different concentrations of rabbit urine and quail manure compost on the chlorophyll content of leaves and the yield of Cabbage (Brassica oleracea var. botrytis L.). The study was conducted in the residential area of RT16/RW.05, Rejowinang Village, Kota Gede Subdistrict, Yogyakarta, Special Region of Yogyakarta. This research was conducted from December 2022 to March 2023. The study employed a 3 × 2 factorial experiment arranged in a Complete Randomized Block Design (CRBD) with four replications. The first factor consisted of three levels of rabbit urine concentration: K0 = control (without rabbit urine concentration), K1 = 30% concentration, K2 = 60% concentration. The second factor involved two levels of quail manure compost dosage: B1 = 5 tons/ha → 1.2 kg/plot, B2 = 15 tons/ha → 3.6 kg/plot. The research results indicate that there is no interaction between the concentrations of rabbit urine and the dosage of quail manure on the chlorophyll content of leaves and the yield of Cabbage plants. The treatments of rabbit urine concentrations (K0), (K1), and (K2) did not show a significantly difference in the chlorophyll content of leaves and the yield of Cabbage plants. Similarly, the dosages of quail manure compost (B1) and (B2) did not show any significantly difference in the chlorophyll content of leaves and the yield of Cabbage plants. Keywords: Cabbage, Rabbit urine POC, Quail manure compost